Induction of Labor Versus Expectant Management After Successful External Cephalic Version. Issue 3 (September 2020) - Barbash-Hazan, S.; Nattiv, N.; Salzer-Sheelo, L.; Bergel, R.; Hadar, E.; Osovsky, M.; Shmueli, A.
Abstract : ( Birth . 2019;46:623–627) External cephalic version (ECV) is a well-established procedure that improves maternal and neonatal outcomes. However, the literature has produced varied results as to the risk and rate of cesarean delivery after successful ECV. Differing results also have been reported when comparing spontaneous labor after ECV versus induction of labor after ECV. The aim of this study was to compare obstetrical and neonatal outcomes after successful ECV among those who underwent immediate labor induction versus those who were managed expectantly.